TAJWEED-BASED ISLAMIC EDUCATION AND THE AUTHENTICITY OF QURANIC MEMORIZATION AT MTS TAHFIZH CENDIKIA PEKANBARU: Linguistic Awareness, Tajwid Internalization, Authenticity of Qur'anic Memorization - Arya Ficky Nugroho Arya; Kadar; Salmaini Yeli (SOSIOEDUKASI, 2026)
This study aims to explore the phenomenon of tajwid internalization in forming students' linguistic awareness and to examine how that awareness functions in preserving the authenticity and long-term durability of Qur'anic memorization at MTs Tahfizh Cendikia Pekanbaru. Employing a qualitative approach with a case study design, data were collected through participatory observation, in-depth interviews with ten tahfizh santri, and documentation of memorization evaluation records, analyzed using the interactive model of Miles, Huberman, and Saldaña, with validity ensured through source and technique triangulation. The findings reveal that tajwid internalization unfolds through three phenomenologically distinct stages, sound recognition, structural comprehension, and full internalization, each progressively constructing a linguistic awareness that functions simultaneously as a phonetic self-monitoring system, a multi-layered mnemonic structure, and a spiritually grounded motivational force. Students who reached full internalization demonstrated autonomous self-correction capacity, sustained memorization retention, and an internalized sense of spiritual responsibility toward recitation authenticity, independent of external evaluation. This study introduces a new theoretical understanding that tajwid is not merely a set of phonetic rules, but a system capable of constructing cognitive and spiritual architecture within the learner.